Pre- & post- retirement tips for librarians - Smallwood, Carol 1939- (Chicago American Library Association, 2012)
"Retirement raises many questions, and each librarian?s situation is unique. Our skills give us an edge in planning as well as managing our lives after library employment. This collection of essays should be an indispensable part of your retirement toolkit."--publishers description.
Exploring your retirement options / Linda Burkey Wade -- Four steps to a better retirement / Brett Hammond -- How to retire graciously / Susan Carol Curzon -- Social security for pre-retirees : basic elements and helpful tips / Donald G. Frank--Your income in retirement : steps to a solid spending plan / Maria A. Bruno -- Investment strategies for fiscally challenged librarians / James B. Casey -- Learning to be frugal : finding the best deals to maintain an active lifestyle / Rose Parkman Marshall -- Maintaining, repairing, and protecting your credit after retirement / Jennifer Boxen -- Following your passion : a dream deferred / Dahlma Llanos-Figueroa -- Going back to school / Louise F. Benke -- Participating in oral histories or donating papers to archives / Dorothea J. Coiffe -- Choosing to go back to work / Sharon Nottingham -- Collecting and selling on eBay : a great career for retired librarians / Jennifer Tang -- Working part-time after retirement / Rita Marsales -- "I thought you retired!" : volunteering in your library / Mary Redmond -- Volunteering in retirement / Renee B. Bush -- My experience volunteering with VSO in Ethiopia / Shirley Lewis --Seven lessons for adjusting to retirement / Janet Husband -- What about health insurance in retirement? / Sandra Cortese -- Logistics of downsizing / Patricia H. Atwood -- Mediation as a tool in legacies and financial planning: a play in three acts / Carolyn J. Rodis and Steven Henick -- The single biggest money mistake retirees make / Brian Fricke -- On the move : relocating when you retire / Susan Montgomery -- Finding the perfect place to retire / Jeanne Munn Bracken.
Keywords: Librarians -- Retirement -- United States; Retirement -- United States -- Planning; Electronic books